Characterization of moment resisting I-beam to circular hollow section column connections resorting to passing-through plates. (1st May 2020) - Das, Rajarshi; Kanyilmaz, Alper; Couchaux, Mael; Hoffmeister, Benno; Degee, Herve
Highlights: A "passing-through" I-beam-to-CHS connection is developed using LCT. "Passing-through" plates are used to connect the main I-beams to the CHS column. Numerical parametric studies are done with experimental validation. Force transfer mechanisms are identified and discussed for different loading. Standard design procedures are proposed based on numerical studies. Joint strength under gravitational load governed by through flange plate. Joint strength under opposite bending load governed by through web plate and CHS. Advantages of the passing-though connection - increased strength and stiffness. Abstract: Open-to-Circular Hollow Section (CHS) connections are highly encouraged nowadays in modern multistoried structures due to the extensive resistance provided by the CHS columns against high compression, tension as well as flexure in all directions, combined with their exceptional aesthetics. However, using more and more gusset plates or stiffeners to strengthen a conventional open-to-CHS connection causes economic disadvantage due to excessive welding quantities and substantial CHS chord yielding further limits any opportunity to exploit the full advantages offered by the open sections therefore minimizing its frequent application. However, if designed efficiently, the CHS connection can offer an extensive range of solutions which makes it an impeccable choice for the modern multi-storey structures. To that purpose, a "LASTEICON" solution is proposed in this paper investigating a "passing-through" concept, which is obtained by using laser cutting technology (LCT). Initially, a suitable moment resisting Plate-to-CHS-column connection is characterized through a detailed understanding of the relevant parameters, where the primary beams are connected at either side of the CHS column by two transverse and one longitudinal plate passing through the CHS column via laser cut slots. A detailed parametric study is conducted based on multiple Finite Element (FE) models primarily calibrated from an experimental campaign to understand the effect of each parameter and further verify and therefore establish the analytical assumptions to calculate the ultimate resistance of such connections. Finally a comprehensive design procedure is proposed to design such "passing-through" Plate-to-CHS column connections. A short comparison study is also made with the conventional (direct weld) joints to highlight the advantages offered by this LASTEICON solution.